Book Reviews - Tambini, Damian and Hart, Jeffrey A. and D’heer, Evelien (International Journal of Digital Television, 2015)
Abstract The Palgrave Handbook of European Media Policy, Karen Donders, Caroline Pauwels and Jan Loisen (eds) (2014) Basingstoke: Palgrave Macmillan, 576 pp., ISBN: 9781137032171, h/bk, £135 The New World of Transitioned Media: Digital Realignment and Industry Transformation, Gali Einav (ed.) (2015) Cham: Springer, 151 pp., ISBN: 9783319090085, h/bk, $129 Political Communication in the Era of New Technologies, Boguslawa Dobek-Ostrowka and Jan Garlicki (eds) (2013) Frankfurt am Main: Peter Lang, 285 pp., ISBN: 98736316441191, h/bk, £41
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qZHR2LjYuMi4yMzlfNQ